2015
DOI: 10.1177/2168479015579520
|View full text |Cite
|
Sign up to set email alerts
|

A Model Data Management Plan Standard Operating Procedure: Results From the DIA Clinical Data Management Community, Committee on Clinical Data Management Plan

Abstract: The model DMP SOP produced addresses most data management issues that are present in any phase clinical trial while providing a flexible framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A third review similar to the DCC overview (Knight) was also reported in 2012 [28]. The Knight review included funding agencies supporting research projects at the London School of Hygiene and Tropical Medicine and was similarly focused on post-publication data management [28] The fourth review by Brandt et al (2015) was limited to DMPs from several pharmaceutical and medical device companies and academic research institutions and resulted in a guideline for writing a standard operating procedure for a DMP that contained recommended topics to be covered in a DMP [29].…”
Section: Introductionmentioning
confidence: 99%
“…A third review similar to the DCC overview (Knight) was also reported in 2012 [28]. The Knight review included funding agencies supporting research projects at the London School of Hygiene and Tropical Medicine and was similarly focused on post-publication data management [28] The fourth review by Brandt et al (2015) was limited to DMPs from several pharmaceutical and medical device companies and academic research institutions and resulted in a guideline for writing a standard operating procedure for a DMP that contained recommended topics to be covered in a DMP [29].…”
Section: Introductionmentioning
confidence: 99%
“…The DMP serves multiple purposes. First and foremost, the DMP comprehensively documents the collection and handling of the data such that every operation performed on data from the time it is collected until finalized as 12 2 The DMP should specify all operations performed on data [V] 12 3 The DMP should be developed in collaboration with involvement from clinical and statistical operations, project management, and scientific study leadership [V] 23 ; The procedure for creating a DMP should be documented in a company or institution's SOP [V] 12 4 An organizational DMP template should be used to ensure consistency and standardization across all projects [V] 12 5 The topics listed in this chapter should be documented in, or referenced by, the DMP [V]…”
Section: ) Purpose Of the Dmpmentioning
confidence: 99%
“…Correspondingly, review and synthesis of DMP requirements in various disciplines and sectors have appeared in the literature. 10,11,12,13 Most notably, Brand et al, 12 reviewed DMPs from several therapeutic development companies and academic research institutions and published a guideline for writing an SOP for DMP creation and maintenance. Williams, et al 13 , on the other hand, broadly reviewed research sponsor DMP requirements with an emphasis on data definition, collection, processing and traceability.…”
Section: ) Introductionmentioning
confidence: 99%
“…An exercise to identify standard requirements for data management systems in clinical trials recommends mechanisms to identify and report on missing or late data, but does not mention maintenance of high data returns throughout a trial [16]. Two recent papers offering advice on data management plan development also do not provide guidance on this issue [17, 18].…”
Section: Introductionmentioning
confidence: 99%